Uncertainty of Geospatial Data in Oil Exploration - Inga Alva, Alexander Eduardo (2018)
The present investigation has focused on the analysis of the uncertainty of geospatial data in the initial stage of oil exploration. Through the evaluation of reliability indices of different data processing methods, a method has been developed that considers Voluntary Geographical Information (VGI) as a new data source and Geodatabase (GDB) as the repository where this information has been validated. With the creation of “Uncertainty Sphere” artifact that has been based on the algorithms of Guide for the Expression of Uncertainty and Measurement (GUM) and the recommendations of ISO 19157: 2013, Geographic Data Quality, Uncertainty Space has been delimited from data collected. The application of a Geographic Information System (GIS) has managed input data (IGV), geospatial processing (artifacts), storage (GDB) and information products (maps). As a case of study, geopositioning uncertainty of Capahuari Sur 3 well of Frontera Energy company has been evaluated and six locations have been validated with GPSLogger and eleven with GPSMap60CSx. These results have allowed the company to consider better scenarios for the drilling of future exploratory wells.